Answer:
Yes they are
Explanation:
In the triangle JKL, the sides can be calculated as following:
=> JK =
![\sqrt{(1-2)^(2) + (1-5)^(2) } = \sqrt{(-1)^(2)+(-4)^(2) } = √(1+16)=√(17)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3j08evcc1c5lf01av58pa79tjm8qi9kgg1.png)
=> JL =
![\sqrt{(5-2)^(2) + (2-5)^(2) } = \sqrt{3^(2)+(-3)^(2) } = √(9+9)=√(18) = 3√(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ueqg3cx2ymzd4ft9cokyg00bqwxqt64hg4.png)
=> KL =
![\sqrt{(5-1)^(2) + (2-1)^(2) } = \sqrt{4^(2)+1^(2) } = √(1+16)=√(17)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b1l60wne0ywes7nso225ox2x4878ufiygf.png)
In the triangle QNP, the sides can be calculate as following:
=> QN =
![\sqrt{[-3-(-4)]^(2) + (0-4)^(2) } = \sqrt{1^(2)+(-4)^(2) } = √(1+16)=√(17)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cad7fgs4tf2ujaukqbfx1p8p23yntcmnto.png)
=> QP =
![\sqrt{[-7-(-4)]^(2) + (1-4)^(2) } = \sqrt{(-3)^(2)+(-3)^(2) } = √(9+9)=√(18) = 3√(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jyehufsrcfo3dqa83fc84we688g7kmlj6z.png)
=> NP =
![\sqrt{[-7-(-3)]^(2) + (1-0)^(2) } = \sqrt{(-4)^(2)+1^(2) } = √(16+1)=√(17)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e0c2deyb4ourli3eljawvoqew58ablcu7r.png)
It can be seen that QPN and JKL have: JK = QN; JL = QP; KL = NP
=> They are congruent triangles